Matches: A Light Book - Chrostowska, S.D (punctum books, 2019)
Through the prism of criticism, the modalities of thinking form a spectrum: on one end, systematic exposition, on the other, the fragment. It is the latter, fragmentary approach that distinguishes Matches-an investigation that does not focus on a single theme developed in all its aspects but, rather, on a constellation of themes in art, literature, philosophy, science, social and political thought, as well as the human in relation to history and nature. The author pursues here in performative fashion her research into the history of critique from the Enlightenment onward. Her choice of the fragment-in the tradition of writing represented by Gracián, Chamfort, Lichtenberg, and, closer to us, Nietzsche, Adorno, and Benjamin-does not, however, stem from an attempt to comprehend the contemporary world, which can only be done after the fact. Instead, served by an expressive and incisive style, Matches foregrounds the necessary elements for a critique of our time, capturing them in their contradictory and complementary relations. It situates itself under the sign of the future, reviving the spirit of utopia, reminding us that the last word need not belong to the present.